2021
DOI: 10.3390/pharmaceutics13111872
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biodistribution, Clearance, and Biocompatibility of Multiple Carbon Dots Containing Nanoparticles for Biomedical Application

Abstract: Current research on the use of carbon dots for various biological systems mainly focuses on the single carbon dots, while particles that contain multiple carbon dots have scarcely been investigated. Here, we assessed multiple carbon dots-crosslinked polyethyleneimine nanoparticles (CDs@PEI) for their in vivo biodistribution, clearance, biocompatibility, and cellular uptake. The in vivo studies demonstrate three unique features of the CDs@PEI nanoparticles: (1) the nanoparticles possess tumor-targeting ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Se-CDs have comparable biocompatibility and more stable chemical characteristics, implying that they are less biotoxic and more suited for the treatment of neurological lesions. 52–54 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se-CDs have comparable biocompatibility and more stable chemical characteristics, implying that they are less biotoxic and more suited for the treatment of neurological lesions. 52–54 …”
Section: Discussionmentioning
confidence: 99%
“…Se-CDs have comparable biocompatibility and more stable chemical characteristics, implying that they are less biotoxic and more suited for the treatment of neurological lesions. [52][53][54] This work developed an injectable hydrogel containing CDs and FTY720 coupled with neural stem cells for treating spinal cord damage. All hydrogels demonstrated good biocompatibility with no internal toxicity or pathological changes after implantation.…”
mentioning
confidence: 99%
“…NPs have various sizes, strong persistence, easy absorption, targeting, and viral similarity, and can replace lentiviral delivery systems to avoid unnecessary immune responses. 21 Among them, AuNPs are the best options for nano-drug delivery because of their unique properties, dexterous synthesis, excellent biocompatibility, ease of cell permeability, and high drug-loading capacity. 22 In vivo, drug absorption is affected by factors such as chemotaxis of intracellular absorption, phagocytosis, and lysosomal fusion time.…”
Section: Discussionmentioning
confidence: 99%
“…88 With regard to CD's toxicity, CDs have great biocompatibility and low cytotoxicity. [89][90][91] A number of in vitro and in vivo cytotoxicity experiments revealed that CDs display toxic effects at high doses but no discernible toxic effect was detected at lower concentrations. The important point is that although there have been few ndings on controlling scaffold cytotoxicity, CD's cytotoxic or disruptive effects on different pathways remain unclear, and need further investigation.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%